2010
DOI: 10.1007/s00348-010-1016-8
|View full text |Cite
|
Sign up to set email alerts
|

Aperiodicity in the near field of full-scale rotor blade tip vortices

Abstract: Blade tip vortices are the dominant vortical structures of the helicopter flow field. The inherent complexity of the vortex dynamics has led to an increasing interest in full-scale in situ experiments, where the near field, closely behind the blade, is of particular interest, since measures of vortex control mostly target this initial stage of development. To examine the near field, threecomponent particle image velocimetry (PIV) measurements of blade tip vortices of a full-scale helicopter in simulated hover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Corrections for this were implemented here using an integral-based approach (the Γ 1 method) that allowed for the vortex centres to be identified; the details of this are described elsewhere (Graftieaux, Michard & Grosjean 2001;Mula et al 2013). Previous studies using multi-bladed rotors have shown the vortex wandering motion to be anisotropic (Kindler, Mulleners & Richard 2010;Mula et al 2013). Similar results are observed here, where figure 2(c) shows the standard deviation of wander along the principal major and minor axes across all vortex ages.…”
Section: Vortex Characteristicssupporting
confidence: 79%
“…Corrections for this were implemented here using an integral-based approach (the Γ 1 method) that allowed for the vortex centres to be identified; the details of this are described elsewhere (Graftieaux, Michard & Grosjean 2001;Mula et al 2013). Previous studies using multi-bladed rotors have shown the vortex wandering motion to be anisotropic (Kindler, Mulleners & Richard 2010;Mula et al 2013). Similar results are observed here, where figure 2(c) shows the standard deviation of wander along the principal major and minor axes across all vortex ages.…”
Section: Vortex Characteristicssupporting
confidence: 79%
“…These findings were consistent with the earlier analytical studies developed on a single helical filament by Widnall (1972). 32 PIV investigations by Kindler et al (2010) 13 and Mula et al (2013) 22 revealed an anisotropic nature of long-wave perturbations (vortex wander) on a plane perpendicular to the vortex filament axis. Further, such an anisotropic nature was found to be insensitive to the choice of the vortex center identification technique.…”
Section: Introductionsupporting
confidence: 91%
“…Mathematical details of the technique are well described by Graftieaux et al (2001) 9 and Kindler et al (2010). 13 Being an integral based approach, the results are not corrupted by noise introduced by gradients of the velocity field. However, the vortex center still relies on an accurate assessment of the velocity inside the vortex core where seeding is poor.…”
Section: A Facility and Instrumentationmentioning
confidence: 99%
“…Substituting T ij ¼ u i u j þ ij ½ð p À p 0 Þ À c 2 ð À 0 Þ À ij into equation (8), we get the following equation:…”
Section: Fem Simulation Of Aerodynamic Noisementioning
confidence: 99%